Implementation of Sauropus Androgynus (Katuk Leaves) as a Non-Pharmacological Intervention to Increase Breast Milk Production in Postpartum Mothers at Pelamonia Hospital Makassar - Sangalia, Landi; Limbong, Magdalena; Kasim, Erna; Nurbaiti, Nurbaiti (LPPM STIKes Muhammadiyah Ciamis, 2025)
Breast milk or mother’s milk is the best source of nutrition recommended for babies from birth to 6 months of age. However, low breast milk production remains a barrier to exclusive breastfeeding, including at RS TK II Pelamonia Makassar. Sauropus androgynus (katuk leaves) is known as a natural ingredient believed to increase breast milk production deu to its active compounds. Identifying how the non-pharmacological implementation of Sauropus Androgynus (katuk leaves) can increase breast milk production in postpartum mothers. This case study used a descriptive method with an observational approach on normal post partum mothers from day 2 to day 7. The intervention involved administering 300 grams of katuk leaf clear soup daily for three consecutive days. The study subjects included two postpartum mothers who met the inclusion criteria: normal postpartum mothers 2–7 days postpartum, primiparous postpartum mothers, postpartum mothers with insufficient breast milk, infants who refuse to breastfeed, and mothers aged 20–35 years. This case study showed a significant increase in breast milk production: Subject I from 9 ml to 78 ml, and Subject II from 13 ml to 86 ml, in addition, there was an improvement in milk output indicators, such as milk leaking, calmer infants, and increased urination frequency. The non-pharmacological use of Sauropus androgynus (katuk leaves) increased breast milk volume in both postpartum subjects. This result suggests that katuk leaves may serve as an effective natural galactagogue. Further research with a larger sample and control group is recommended.